DRY MILK WHEY - Razzakov Amirjon Elbekjonovich; Rakhmonov Farkhod Kholbaevich (Western European Studies, 2025)
The article presents a review of studies devoted to dry whey, a valuable by-product of the dairy industry. Dry whey is a white powder obtained during the processing of cheese and milk. It is a by-product of the production of cheese, cottage cheese, and butter. Depending on the product being produced, cheese, cottage cheese, or butter whey is obtained.
Keywords: Dry milk whey; properties; composition